2022
DOI: 10.1097/j.pain.0000000000002688
|View full text |Cite
|
Sign up to set email alerts
|

Combination pharmacotherapy for the treatment of neuropathic pain in adults: systematic review and meta-analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 70 publications
(735 reference statements)
0
15
0
Order By: Relevance
“…Although this trial provides no evidence to support the use of a pregabalin-ALA combination for neuropathic pain, the results do help inform the development of future combination therapy strategies. Previous trials involving combinations of first-line neuropathic pain drugs, such as anticonvulsants and antidepressants, have shown that-in flexible dose-titration trialsmaximally tolerated drug doses during combination therapy lower than during monotherapy 2,14 or-in fixed dose-titration trials-treatment-related adverse effects are more frequent or severe during combination therapy. 2 In this trial, we have demonstrated that, in a combination of drugs with differing adverse effect profiles, doses can be titrated to similarly tolerated levels as with monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this trial provides no evidence to support the use of a pregabalin-ALA combination for neuropathic pain, the results do help inform the development of future combination therapy strategies. Previous trials involving combinations of first-line neuropathic pain drugs, such as anticonvulsants and antidepressants, have shown that-in flexible dose-titration trialsmaximally tolerated drug doses during combination therapy lower than during monotherapy 2,14 or-in fixed dose-titration trials-treatment-related adverse effects are more frequent or severe during combination therapy. 2 In this trial, we have demonstrated that, in a combination of drugs with differing adverse effect profiles, doses can be titrated to similarly tolerated levels as with monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, current combination prescribing is based on little evidence, some combinations may be harmful, and authorities have demanded more research to develop rational combination strategies. 12 Although previous trials support the merits of some drug combinations, 2 several neuropathic pain drugs (eg, anticonvulsants and antidepressants) cause similar adverse effects such that patients can only tolerate lower drug doses during combination therapy (vs monotherapy), thus limiting the magnitude of additive analgesia. 2,17 Therefore, we have postulated that combining agents with differing adverse effect profiles (eg, 1 sedating plus 1 nonsedating drug) to treat neuropathic pain will result in even greater additive analgesia because maximal doses of each drug can be tolerated during combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…NP remains a challenging condition to treat, with current recommended pharmacological therapies providing only partial relief from pain, sometimes exacerbating other symptoms [ 41 ]. To the best of our knowledge, this proposed RCT is the first to investigate the safety and efficacy of melatonin for the treatment of NP.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, pharmacologic intervention seldom achieves complete resolution of neuropathic pain due to limited efficacy, dose-limiting adverse events, or both [119][120][121]. Therefore, a standardized approach to combining pharmacotherapies is an unmet medical need and remains an area of intense study [122][123][124]. Spinal cord stimulation is an emerging therapeutic adjunct for the management of PDN [125].…”
Section: Principle 3: Individualized Treatment and Scheduled Follow-upmentioning
confidence: 99%